Comparison of plasma responses in human subjects after the ingestion of 3R,3R′-zeaxanthin dipalmitate from wolfberry (Lycium barbarum) and non-esterified 3R,3R′-zeaxanthin using chiral high-performance liquid chromatography - Breithaupt, Dietmar E.; Weller, Philipp; Wolters, Maike; Hahn, Andreas (British journal of nutrition, 2004)
Age-related macular degeneration (AMD) is one of the most common eye diseases of elderly individuals. It has been suggested that lutein and zeaxanthin may reduce the risk for AMD. Information concerning the absorption of non-esterified or esterified zeaxanthin is rather scarce. Furthermore, the formation pathway of meso (3R,3′S)-zeaxanthin, which does not occur in plants but is found in the macula, has not yet been identified. Thus, the present study was designed to assess the concentration of 3R,3R′-zeaxanthin reached in plasma after the consumption of a single dose of native 3R,3′R-zeaxanthin palmitate from wolfberry (Lycium barbarum) or non-esterified 3R,3′R-zeaxanthin in equal amounts. In a randomised, single-blind cross-over study, twelve volunteers were administered non-esterified or esterified 3R,3′R-zeaxanthin (5 mg) suspended in yoghurt together with a balanced breakfast. Between the two intervention days, a 3-week depletion period was inserted. After fasting overnight, blood was collected before the dose (0 h), and at 3, 6, 9, 12, and 24 h after the dose. The concentration of non-esterified 3R,3′R-zeaxanthin was determined by chiral HPLC. For the first time, chiral liquid chromatography–atmospheric pressure chemical ionisation-MS was used to confirm the appearance of 3R,3′R-zeaxanthin in pooled plasma samples. Independent of the consumed diet, plasma 3R,3′R-zeaxanthin concentrations increased significantly (P=0·05) and peaked after 9–24 h. Although the concentration curves were not distinguishable, the respective areas under the curve were distinguishable according to a two-sided F and t test (P=0·05). Thus, the study indicates an enhanced bioavailability of 3R,3′R-zeaxanthin dipalmitate compared with the non-esterified form. The formation of meso-zeaxanthin was not observed during the time period studied.